2013
DOI: 10.1177/0256090920130307
|View full text |Cite
|
Sign up to set email alerts
|

Grassroots Innovations for Inclusive Development: Need for a Paradigmatic Shift

Abstract: After considering about 6,000 patents granted and applied for during 1998-2008, around 250 creative people were invited and the first such workshop led to the setting up of the Centre for Innovation, Incubation and Entrepreneurship (CIIE) at IIMA with the initial grants from NIF and the Gujarat Government. The idea was to focus on mass impact and high-tech innovations. The social capital created by research on grassroots innovation came in handy to persuade the Gujarat Government to consider supporting the Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 9 publications
0
6
0
4
Order By: Relevance
“…Local communities need to be in forefront towards knowledge creation, distribution and sharing system (Lwoga et al, 2010). Creative expressions of informal society can provide solutions and accessibility to appropriate technology (Kumar et al, 2013). Previous research results revealed several plants that can be used reliably and safely to treat livestock.…”
Section: Discussionmentioning
confidence: 99%
“…Local communities need to be in forefront towards knowledge creation, distribution and sharing system (Lwoga et al, 2010). Creative expressions of informal society can provide solutions and accessibility to appropriate technology (Kumar et al, 2013). Previous research results revealed several plants that can be used reliably and safely to treat livestock.…”
Section: Discussionmentioning
confidence: 99%
“…According to Gupta [4], GRI is a unique concept in having environment-friendly solutions to the local problems of grassroots communities. Furthermore, it is noted that networking is vital for GRI to receive monetary and non-monetary resources from the government organizations, non-government organization and communities [14,18]. It is also evident that success of GRI depends on the level of socio-economic exchange between the network actors that facilitate grassroots development.…”
Section: Grassroots Innovation (Gri)mentioning
confidence: 99%
“…The essence of the GRI is the process of innovation by which the grassroots people such as the rural people, the marginalized communities and the indigenous tribes in rural and semi-urban areas can alter their economic destitution and access a better quality of life [18,19]. Grassroots innovators have the potential for innovations born out of necessity, but they require resources to cmmercialize that innovation or its products [6,20].…”
Section: Grassroots Innovation (Gri) and Entrepreneurshipmentioning
confidence: 99%
“…These could be grass roots innovations (Kumar et al, 2013), service or organizational innovations;  To mobilize marginalized sections of society (poor people, workers and farmers) and organize them into different institutional structures (selfhelp groups, cooperatives, etc.) to enable them to improve their livelihoods and income through various skill and non-skill-based activities; and  To make accessible the benefits of modern science, technology and medicine to poor and underprivileged sections by various institutional measures.…”
Section: Introductionmentioning
confidence: 99%